The degree of application of quality standards in electronic supervision in light of the Corona pandemic: a study in education offices in the Kingdom of Saudi Arabia - Almasod, Basma Thamer Nzal (Journal of Educational and Psychological Sciences, 2022)
The study aimed to assess the extent to which quality standards are applied in electronic supervision in considering of the Corona pandemic in education offices in the Kingdom of Saudi Arabia. The results of the study: that the degree of application of quality standards in electronic supervision in light of the Corona pandemic in education offices in the Kingdom of Saudi Arabia came to a very large degree with an approval rate of 87.6%, and in light of the previous results, the researcher recommended the necessity of urging the educational supervisor to motivate teachers to use the means advanced technology and providing them with educational developments in their field of specialization.
Keywords: quality standards; electronic supervision; corona pandemic